Exploring the combined effort of authentic leadership and psychological capital on job satisfaction mediated by job stress, in Bangladesh, pharmaceutical industry - Sultana, Umme Salma (2019)
This study aims to investigate the combined effort of authentic leadership and psychological capital in decreasing job stress and increasing job satisfaction in the context of the pharmaceutical industry in Bangladesh. This quantitative study employed the use of a questionnaire in order to determine relationship between these variables. The questionnaires were sent to the respondents via email in order to collect data from mid-level employees who are working with pharmaceutical companies in Bangladesh. They were asked to complete the questionnaire anonymously. A total of 870 questionnaires were distributed to all the potential respondents. A total of 242 questionnaires were returned from which 215 were selected as appropriate for data analysis. Structural Equation Modelling (SEM) approach was used to test the conceptual framework while SmartPLS 3 was used to test the hypotheses. The findings from overall measurement model and structural model analysis indicate that all components of the authentic leadership and psychological capital significantly decrease job stress. In addition, authentic leadership and psychological capital partially increase job satisfaction directly. However, when job stress mediates the relationship between authentic leadership and job satisfaction and between psychological capital and job satisfaction, all other components significantly increase job satisfaction, with the exception of Optimism. The results provide evidence that authentic leadership and psychological capital should be practiced holistically to decrease job stress and increase job satisfaction in the context of the pharmaceutical industry in Bangladesh. This study offers a deep understanding of the relationship between authentic leadership, psychological capital, job stress, and job satisfaction and the findings of this study add to the pool of knowledge related to the effects of authentic leadership and psychological capital towards job stress and job satisfaction in both theory and practice.